Re-annotation for hypothetical protein CA803_03125 of Methicillin-Resistant Staphylococcus aureus strain SO-1977 isolated from Sudan - Mohamed, Sofia B (Bioinformation, 2019)
This study aims to describe the global detection and functional inference of hypothetical protein CA803_03125 from Staphylococcus aureus SO-1977. Computational methods were utilized to study this protein based on sequence similarity and presence of known protein domains. The BLASTp result revealed a significant similarity between the hypothetical protein (CA803_03125) and ADP-ribose hydrolase protein from four S. aureus strains (MW2, MRSA252, COL, and N315). Evolutionary tree diagram revealed a close relationship between the hypothetical protein and proteins of MW2 and COL strains. The physicochemical characterization revealed that all proteins were found to be stable, soluble, hydrophilic and acidic in their nature. The Macro domain was found to exist within all proteins. Moreover, the proteins were of pronounced similarity in terms of primary, secondary and tertiary organization. The protein CA803_03125 (SO-1977) is already known and well characterized as ADP-ribose hydrolase; therefore, we would recommend that its NCBI data has to be updated to be submitted under the name of ADP-ribose hydrolase.